Research on Cultural Translation Based on Neural Network. (23rd April 2022) - Wang, Junya
Abstract : The translation of pragmatic meaning requires the processing of pragmatic implicit meaning, the translator's responsibility for the readers of the target language to understand the pragmatic meaning, and the domestication and foreignization of cultural images. The way of pragmatic language equivalence is domestication translation to achieve the fluency of language expression. The creation of foreignized translation in order to foster the equitable interchange and dissemination of culture, which is precisely the aim of cultural translation, is the equivalence of the pragmatic meaning of cultural imagery. Neural network (NN) machine translation technology (MTT) simulates the human brain nervous system. Based on deep learning technology, the whole sentence is used as the basic unit of translation, which greatly improves the accuracy of machine translation. This paper selects the relevant texts of Shaanxi's red tourism culture and uses the NN translation system to translate. It helps to improve the accuracy of the text translation of Shaanxi red tourism culture by analyzing the translation and providing a reference direction for further revision by neural translation users and promote the overseas dissemination of red culture. The part of the source language side that generates a vector representation of a dense and continuous sentence from the input corresponds to the encoder.